‘Goals of Care’ Discussion in Surgical Settings: A Pilot Curriculum for the Training of the Faculty Members and Residents under Faculty of Surgery (Mugda Medical College Journal, 2025)
Early consideration and communication about goals, values, and treatment preferences in the surgical settings can prevent patients (who are suffering from incurable disease e.g., terminal stages of cancer) from undergoing unwanted and unnecessary interventions and help them discuss their priorities (themselves, or along with family members or through surrogate decision-makers). However, there is no (bio)ethics curriculum/training in clinical education in Bangladesh to address the specific needs of the professionals to gain knowledge and skills in ‘goals of care’ discussion. Hence, this (bio)ethics education and training is intended to train surgical faculties and residents to enhance their knowledge, skills, and attitude towards ‘goals of care’ (GOC) conversations (near end of life). Ethics and values play crucial roles in ‘goals of care’ discussion. High quality care can only be achieved when a patient’s care is aligned with their goals, preferences, and values. Physicians do have thoroughly entrenched values like promoting health and reducing suffering, while patients may have some values of life, family connections, and religious or cultural beliefs. The prominent ethical principles behind the ‘goals of care’ discussion are: patient’s autonomy (patient’s choices and preferences based on his/her values of life, engagement of family members, or living in according with religious beliefs or cultural norms), beneficence (care planning aligning with patient’s disease course and prognosis), non-maleficence (avoiding unnecessary and unwanted interventions in terms of surgery or other therapies and resuscitation procedures) and distributive justice (in terms of resource allocation, e.g., unnecessary occupancy of hospital bed/ICU). This curriculum has been designed in a way that it is expected to enhance awareness about those ethical challenges based on ‘principlism’, and ways to overcome those challenges, which will ultimately lead to better communication skill, physician-patient relationship, improve patient safety and outcomes, and optimize the cost-effectiveness of organizational resources.Mugda Med Coll J. 2025; 8(2): 133-137